AKTIVITAS ANTIBAKTERI EKSTRAK KAYU SECANG ( Caesalpinia sappan L.) TERHADAP BAKTERI Edwardsiella tarda DAN Edwardsiella ictaluri PATOGEN BUDIDAYA PERIKANAN - Sazali, Ahmad; Adriadi, Ade; Yusuf, Ashif Irvan; Maritsa, Hasna Ul; Siringo-ringo, Annisa Juliana; Kise, Hanny Faatihah (Berita Biologi, 2024)
The disease caused by pathogenic bacteria is one of the main problems in aquaculture in the Jambi Province. One of the diseases that occurs in cultivated catfish is due to infection by bacteria Edwardsiella tarda and Edwardsiella ictaluri, which cause Edwardsiellosis with a mortality rate above 50%. The antibacterial properties of the sappanwood extract (Caesalpinia sappan, L.) can be used to overcome problems in aquaculture, while reducing the use of antibiotics that can have negative impacts. This research aims to explore the antibacterial potential of sappanwood extract (Caesalpinia sappan, L.), a local plant believed to possess strong antimicrobial activity. The study began with isolating bacteria from catfish that showing symptoms of the disease, identifying the test bacteria, followed by extracting sappanwood using 96% ethanol solvent. Subsequently, the antibacterial activity was tested using the disc diffusion method with extract concentrations of 1%, 5%, and 10%. The research results indicate that sappanwood extract at a concentration of 5% has a very strong ability to inhibit the growth of E. tarda and E. ictaluri bacteria. The inhibition zones produced show significant antibacterial activity equivalent to the antibiotic ciprofloxacin used as a positive control.